Rubella virus contains one capsid protein and three envelope glycoproteins, E1, E2a, and E2b. - Oker-Blom, C (1983)
We have analyzed the structure of rubella virus proteins labeled metabolically with [35S]methionine, [3H]mannose, and [3H]glucosamine or externally with [3H]borohydride after galactose oxidase treatment. Four structural proteins, with MrS of about 58,000 (E1), 47,000 (E2a), 42,000 (E2b), and 33,000 (C), were resolved on sodium dodecyl sulfate-polyacrylamide gels. Tryptic peptide maps obtained from [35S]methionine-labeled proteins indicated that E1 and C were unrelated to each other and to E2a and E2b, whereas the latter two gave similar, if not identical, maps. E1, E2a, and E2b were associated with the envelope and were located externally on the virus particle, whereas the C protein was associated with the RNA in the nucleocapsid. Solubilization of the virus with Triton X-100, followed by removal of the nucleocapsid and the detergent, resulted in the formation of soluble envelope protein complexes (rosettes) containing E1, E2a, and E2b. Although external labeling with [3H]borohydride and metabolic labeling with [3H]glucosamine suggested that all three proteins were glycosylated, only E1 and E2b were efficiently labeled with [3H]mannose. It is thus possible that the difference in migration between E2a and E2b is due to differences in glycosylation. Analysis by immunoprecipitation and sodium dodecyl sulfate-gel electrophoresis of intracellular [35S]methionine-labeled structural proteins synthesized in the presence and absence of tunicamycin supported the conclusion that E1 and E2 are glycoproteins. Unglycosylated E1 and E2 had an Mr of about 53,000 and 30,000, respectively.